COMMUNITY SERVICE EDUCATION ASSISTANCE OF MRS. PRIMIPARA IN RECOGNIZING HIGH RISKS AND THE SUCCESS OF IMD IN THE WORK AREA OF THE HEALTH CENTER THE FIELD - Palupi Bodro Sayekti; Leni Agustina; Winda Azhari (Jurnal Masyarakat Indonesia (Jumas), 2025)
Primitive mothers often face anxiety and unpreparedness in facing the labor process and the postpartum period, especially in recognizing the signs of high risk and the importance of the success of Early Breastfeeding Initiation (IMD). The lack of comprehensive education is often a major obstacle in optimizing maternal and newborn health. This community service activity aims to improve the knowledge and skills of primipara mothers in recognizing the high risk of pregnancy and support the success of IMD as the first step in infant health. The program will be carried out on August 20, 2025 in the working area of the Medan Tuntungan Health Center with interactive counseling methods, IMD technique demonstrations, and group discussions. The results of the evaluation showed a significant increase in participants' understanding of early detection of high risk and understanding of the clinical benefits of IMD. This education has succeeded in increasing the confidence of primipara mothers in preparing for safe childbirth and supporting exclusive breastfeeding from an early age.